Management of seed borne fungal pathogens of okra collected from seed companies (Asian Journal of Medical and Biological Research, 2016)
Effect of mehogoni, mehedi and allamanda extracts were tested to control seed borne fungi of okra seeds collected from 6 companies of notunbazar in Mymensingh district. Prevalence of seed borne fungi was studied by blotter method in the Seed Pathology Center (SPC) and MS Laboratory, Department of Plant Pathology, Bangladesh Agricultural University (BAU), Mymensingh. The highest germination percentage was recorded from ACI seeds (88%), while lowest (70%) in BADC seeds. Six predominant fungal genera were identified. These species were Fusarium oxysporum (5.08%), Aspergillus flavus (4.50%), Aspergillus niger (6.50%), Colletotrichum dematium (4.67%), Rhizopus stolonifer (3.33%) and Penicillium spp. (3.00%). Germination percentage and fungal association varied from company to company. The germination was ranged from 70-95% and infections were recorded 0.80-6.1% in all the treated seeds. Mehogoni extracts at the rate of 1:1 showed best performance in increasing seed germination (96.00%) next to allamanda (70%). Vigour index of okra seeds were increased 19.14% over untreated seeds by the treatment of mehogoni seed extracts at the rate of 1:1. Mehogoniseed extract at the rate of 1:1 seemed to be adoptable at the farmer?s level as an organic management practice.Asian J. Med. Biol. Res. December 2015, 1(3): 628-640